TINJAUAN KOREOGRAFI TARI MENJEMPUT INDUK PADI KARYA IRA IRMAWATI (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study aims to analyze and describe the choreography of the Menjemput Induk Padi Dance created by Ira Irmawati. This research employed a qualitative approach using a descriptive method. The research instrument was the researcher, supported by stationery and a mobile phone. Data were collected through literature review, observation, interviews, and documentation. The data analysis procedures included data collection, data reduction, data presentation, and conclusion drawing. The results of the study indicate that the choreography of the Menjemput Induk Padi Dance consists of the choreography process and the choreography form. The choreography process includes theme/idea, exploration, improvisation, and composition. The theme and idea originated from the traditional ritual performed by the people of Rantau Panjang Village before harvesting rice in the umo (rice field). The movements of the Menjemput Induk Padi Dance were developed through exploration of various movement forms depicting rice plants in the fields. The choreographer carried out improvisation by experimenting with new movement patterns, which were further developed based on her creativity. The dance composition was arranged using various creative movement patterns. In terms of choreography form, the Menjemput Induk Padi Dance consists of 11 movement sequences for the male dancer and 34 movement sequences for the female dancers, all of which have undergone stylization. The upper designs found in the dance include angular, curved, high, low, flat, medium, contrasting, vertical, and horizontal designs. The dance also employs 48 floor patterns performed by the dancers. The dramatic design is divided into three sections. The dance dynamics are predominantly characterized by a fast tempo, strong energy, and medium level. The group compositions include unison, canon, alternate, broken, and balance. The musical accompaniment consists of gendang dap, gendang tabuh, gong, canang, wooden kelintang, kompang, accordion, violin, wooden flute, and electric bass. The costumes are adapted from traditional Jambi Malay attire. The properties used include tunam—the principal property that must always be present—seven-colored cloth, and a water jug (kendi), which is believed by the people of Rantau Panjang to symbolize the "rice goddess." The makeup in the Menjemput Induk Padi Dance serves to emphasize the dancers' expressions, character, and beauty while reinforcing the sacred atmosphere and cultural values of the performance.